Reagent-free determination of amikacin content in amikacin sulfate injections by FTIR derivative spectroscopy in a continuous flow system - José F. Ovalles; Máximo Gallignani; MarÃa R. Brunetto; Rebeca A. Rondón; Carlos Ayala (Elsevier, 2014)
The quantitative estimation of amikacin (AMK) in AMK sulfate injection samples is reported using FTIR-derivative spectrometric method in a continuous flow system. Fourier transform of mid-IR spectra were recorded without any sample pretreatment. A good linear calibration (r>0.999, %RSD<2.0) in the range of 7.7â77.0Â mg/mL was found. The results showed a good correlation with the manufacturer's and overall they all fell within acceptable limits of most pharmacopoeial monographs on AMK sulfate. Keywords: Amikacin, FTIR derivative spectrometry, Continuous flow system, Pharmaceutical preparation, Injection, Sulfate